If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-4)+3(x-4)=3(x+6)+2
We move all terms to the left:
4(x-4)+3(x-4)-(3(x+6)+2)=0
We multiply parentheses
4x+3x-(3(x+6)+2)-16-12=0
We calculate terms in parentheses: -(3(x+6)+2), so:We add all the numbers together, and all the variables
3(x+6)+2
We multiply parentheses
3x+18+2
We add all the numbers together, and all the variables
3x+20
Back to the equation:
-(3x+20)
7x-(3x+20)-28=0
We get rid of parentheses
7x-3x-20-28=0
We add all the numbers together, and all the variables
4x-48=0
We move all terms containing x to the left, all other terms to the right
4x=48
x=48/4
x=12
| 4d+50=-270 | | 6x^2-4=22x | | 4(x-4)+3(x-4)=3 | | 9k-4k-5=10 | | 22÷x+3=14 | | (3m-1)-m+2=0 | | (x+27)+(2x-7)=90 | | 7x²+18x-530=0 | | 8x+21= | | F(x)=30x10 | | -4x=14=54 | | N=40(m+7) | | -5v-(-7-4v)=-2(3v-4) | | 4^4=16^x | | 2n-3=n=2 | | x/2+1=x/5+1/4 | | 7x=x+x+x+24 | | 4=b17 | | 59-u=287 | | 6x-37=-5(2-3x) | | -2(4f-6)=36 | | (6x-1)+(5x+28)=90 | | 2(x+21)= | | x13=6 | | 4v−5=3v+4 | | (x+1)(x-7)=(x+1)(x-3) | | 11x-79=6x-47 | | 3(f+5)=18 | | 2x(x+15)=55+x | | 22=u/3+17 | | 180=15n | | 5x–3x+8=4+4x–6 |